What does it mean to be a “citizen of the world”: A prototype approach - Carmona, M.; Guerra, R.; Hofhuis, J. (Journal of Cross-Cultural Psychology, 2022)
The superordinate social category “citizen of the world” is used by laypeople and scholars to embody several constructs (e.g., cosmopolitanism; global identity and citizenship), and prior research suggests that the concept is better represented as a prototype rather than having a clear-cut definition. This research aims to systematically examine the prototypical meaning of this social category, and how it is cognitively processed. Relying on a prototype approach, six studies (n = 448) showed that certain attributes of this category were communicated more frequently and were regarded as more central (e.g., multiculturalism), and that central (vs. peripheral) attributes were more quickly identified, more often remembered, and more appropriate to identify a group member, as well as the self, as a “citizen of the world.” These results systematically demonstrated that this category has a prototypical structure and there is a differentiated cognitive automatic processing for central and peripheral attributes. We propose that the specific content activated by the attributes regarded as central to the prototype of “citizens of the world” (e.g., intercultural contact; diversity), and the fact that these are more accessible in memory to form a mental representation, are important aspects to understand identity processes and their impact on intergroup outcomes.